Hubungan Menyusui Langsung oleh Ibu dan Menggunakan Pacifier dengan Perkembangan Bicara Pada Bayi Usia 0-6 Bulan - Wati, Anis Kurnia, Agus Widodo, S.Fis, M.Kes (2017)
BACKGROUND: Speaking ability was built through acquisition process in early stage. The prevalence of speech delay is estimated 3-10% in around the world. The exclusive breastfeeding decreases continuously from year to year due to several factors such as mothers choose using pacifier that contains breast milk or formula milk. Critical period of listening and speaking development starts from the first 6 month of life. Baby who had delayed which intervened before 6 months old, when they are 3 years old will have normal language skill if compared with the baby who intervened after 6 months old. PURPOSE: To know the relationship direct breastfeeding by mothers and use pacifier with the speech development of baby aged 0-6 months. SUBJECT: 0-6 month baby who visited in PKU Muhammadiyah Wonogiri Hospital from 15 November until 15 December, obstained subject 60 babies were divided into 3 groups, each group was given 20 respondents direct breastfeeding by mothers, direct breastfeeding by mothers +pacifier, and pacifier. METHODS:This study was observational with cross sectional approach. The sampling technique is using quota sampling, investigators identified to be met from the sampling of the population that met the criteria of inclusion and exclusion. The measurement of speech development is done by using Early Language Milestone Scale-2 (ELMS-2). Data analysis technique is using Chi Square test. RESULTS:Total respondents were 60 babies and the babies who had speech delay were 27 babies (45%). The respondent who got speech delay mostly the babies who use pacifier, there are 13 babies. Ρvalue 0.028 with the significance (α) 0.05, which means that there is a relationship significance between direct breastfeeding by mothers and use pacifier with Early Language Milestone Scale-2 (ELMS-2) assessment. CONCLUSION:There is a relationship direct breastfeeding by mothers and use pacifier with speech development of baby aged 0-6 months. KEY WORDS: breastfeeding, pacifier, speech delay, ELMS-2.